Proposed Financial Education Program for Selected Rice Farmers in The Municipality of Bongabong - Melendres, Jared (ADPEBI International Journal of Business and Social Science, 2024)
ABSTRACT Purpose – The study determined the relationship of their profile, level of financial literacy, and extent of financial literacy practices to the level of financial standing of the selected rice farmers in Municipality of Bongabong. Methodology/approach – The study surveyed 84 selected rice farmers in Municipality of Bongabong. The study used descriptive-correlational research design, and percentage, weighted mean, and multiple regression for the treatment of data. A survey questionnaire, interview and focus group discussion were made in data gathering. Findings – The study revealed that selected rice farmers have remarkably high levels of financial literacy in terms of budgeting, savings, and debt management. Also, the selected rice farmers have strong financial position in terms of income, indicating that rice farming and their other sources of income generate a lot of money. However, it was found to be low in terms of social security, financial risk management, and investing. Moreover, their ability to cope with farming and household expenses, as well as savings, are limited. The study concluded that income and financial literacy knowledge in terms of borrowing had a positive influence on rice farmers' financial standing; thus, increased income generation and financial knowledge are essential to sound financial well-being. Novelty/value – Based on the findings, the researcher proposed a financial education program tailored to the needs and circumstances of rice farmers. With this, issues in financial constraints of the rice farmers could be addressed through the community extension focused on financial education.